Switching on thermal and light-induced spin crossover by desolvation of [Fe(3-bpp)2](XO4)2·solvent (X = Cl, Re) compounds. Issue 13 (2nd June 2021) - Djemel, Abdelhak; Stefanczyk, Olaf; Desplanches, Cédric; Kumar, Kunal; Delimi, Rachid; Benaceur, Farouk; Ohkoshi, Shin-ichi; Chastanet, Guillaume
Abstract : Two new complexes [Fe(3-bpp)2 ](XO4 )2 ·solv (X = Cl, 1 and Re, 2 ) have been prepared. Both systems show desolvation-assisted spin crossover (DASCO) and light-induced excited spin-state trapping (LIESST) phenomena. Abstract : Thermal desolvation is a very attractive method for the post-synthetic modification of the physicochemical properties of switchable materials. In this field of research, special attention has been paid to the possibility of modifying the thermo- and photo-induced spin crossover (SCO) properties of metal complexes as they can act as solvent sensors. Two new [Fe(3-bpp)2 ](ClO4 )2 ·2.5H2 O·MeOH (1·sol ) and [Fe(3-bpp)2 ](ReO4 )2 ·3H2 O (2·sol ) compounds, where 3-bpp is 2, 6-di-(1 H -pyrazol-3-yl)pyridine, were prepared and structurally characterized, and their solvated and desolvated phases were additionally investigated spectroscopically, magnetically and photomagnetically. Single-crystal X-ray structures of 1·sol and 2·sol consist of similar [Fe(3-bpp)2 ] 2+ units arranged in π–π stacked layers separated by H-bond-stabilised layers consisting of solvent molecules and anions. Moreover, both materials show desolvation-assisted SCO from a low (LS, S = 0) to high-spin state (HS, S = 2) at around 340 K, followed by a reversible gradual spin conversion with T 1/2 ≈ 210 K and 304 K for 1 and 2, respectively. Photomagnetic studies of 1·sol and 1 confirmed the efficiency of the light-induced excited spin-state trapping (LIESST) phenomenon with relaxation temperatures T (LIESST) = 82 K and 66 K for the solvated and desolvated phases, respectively. In the case of 2·sol, no LIESST effect was observed while the desolvated phase 2 exhibits a LIESST behaviour at T (LIESST) ≈ 50 K.